1983
DOI: 10.1126/science.6849116
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Bioactivation of S -Alkyl Phosphorothiolate Pesticides: Stereospecificity of Profenofos Insecticide Activation

Abstract: The mouse liver microsomal mixed-function oxidase system converts several phosphorothiolate pesticides with S-ethyl, S-propyl, or S-butyl groups to more potent inhibitors of acetylcholinesterase. This activation is stereospecific for the chiral isomers of O-(4-bromo-2-chlorophenyl) O-ethyl S-propyl phosphorothiolate (profenofos insecticide); the more toxic (-) isomer becomes a 34-fold better inhibitor of acetylcholinesterase in vitro, whereas the less toxic (+) isomer is deactivated by a factor of 2. Prior tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
52
0

Year Published

1991
1991
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(54 citation statements)
references
References 12 publications
2
52
0
Order By: Relevance
“…Methamidophos, however, contrary to other S-alkylphosphorothiolates, is not activated to more potent AChE inhibitors by mouse liver microsomes (Wing et al 1982) or by hen liver microsomes (our unpublished results).…”
Section: Discussionmentioning
confidence: 69%
“…Methamidophos, however, contrary to other S-alkylphosphorothiolates, is not activated to more potent AChE inhibitors by mouse liver microsomes (Wing et al 1982) or by hen liver microsomes (our unpublished results).…”
Section: Discussionmentioning
confidence: 69%
“…This is due to the preferential sulfoxidation of (−)-profenofos in vivo, resulting in a metabolite that is up to 34 times more inhibitory to AChE Fosthiazate pk1 > pk2 > pk4 > pk3 CD and LPD Daphnia magna Acute toxicity; in vitro inhibition of electric eel acetylcholinesterase not stereoselective; has 4 stereoisomers due to presence of P and C chiral centers; stereoisomers identified based on elution order on Chiralpak ® AD column [35] Chloramidophos pk3 > pk2 > pk1 > pk4 CD Daphnia magna Acute toxicity; has 4 stereoisomers due to presence of P and C chiral centers; stereoisomers identified based on elution order on Chiralpak ® AD column [36] a CD: circular dichroism detector; LPD: laser polarimeter detector. [67]. The same study also showed the preferential detoxification of (+)-profenofos.…”
Section: Enantioselective Insecticidal Activitymentioning
confidence: 61%
“…Like profenofos, methamidophos also contains a sulfur substituent to the chiral P in its structure, and may be subject to similar bioactivation processes as previously described here for profenofos [5,67] (Fig. 1).…”
Section: Enantioselective Non-target Toxicitymentioning
confidence: 75%
“…Esterases responsible for detoxification of temephos in this study may be inhibited by DEF with or without induction by BZT. Many phosphorothiolates, including DEF, can be converted to highly potent esterase inhibitors by P450 catalysis (Hur et al, 1992;Wing et al, 1983). If this is the case, BZT may induce P450s that carry out oxidative bioactivation of DEF.…”
Section: Discussionmentioning
confidence: 97%